The Impact of Credit Constraint on Productivity and Technical Efficiency of Sugarcane in Indonesia - Indah Maharani; Kusnadi, Nunung; Fariyanti, Anna (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Credit constraints on banks in the sugarcane plantation sector hinder efforts to achieve sugar self-sufficiency. Farmers' access to banking is often deemed difficult due to the dominance of small-scale farmers who lack collateral. In reality, farmers who successfully access banking sources also face constraints as the amount of credit received does not match the amount requested due to information imperfections between banks and farmers. Therefore, this research aims to identify the characteristics of farmers facing credit constraints, analyze the impact of credit constraints on productivity and technical efficiency, and identify the factors influencing technical inefficiency. The sample size consists of 4885 farmers who were then analyzed using ordinal probit regression, stochastic frontier analysis (SFA), total factor productivity (TFP), partial productivity, and propensity score matching (PSM) methods. Based on the research findings, it can be concluded that land area and participation in agricultural organizations such as cooperatives and partnerships strengthen the degree of credit constraint. Meanwhile, land ownership and irrigated decrease the degree of credit constraint. The negative impact of credit constraints on productivity and technical efficiency is evident. Factors influencing technical efficiency include land status, land type, seed varieties, and participation in cooperatives and partnerships. This research has implications for bank policies that should not hinder farmers' access to banking services. This can be achieved by designing specific agricultural loans that view agriculture not as a risk but as a long-term investment. Keywords: credit constraint, propensity score matching (PSM), stochastic frontier analysis (SFA), technical efficiency